Nitrogen-Doped Graphene via In-situ Alternating Voltage Electrochemical Exfoliation for Supercapacitor Application - Jing, Mingjun; Wu, Tianjing; Zhou, Yazheng; Li, Xilong; Liu, Yong (Frontiers in Chemistry, 2020)
Doping heteroatom is one of effective ways to enhance the electrochemical performances of graphene, which has been received widely attention, especially nitrogen. Alternating voltage electrochemical exfoliation, as a low cost and green electrochemical approach, has been applied to in-stiu obtain N-doped graphene (N-Gh) material. The N-Gh presents much higher capacity than that of pure graphene prepared via the same method, which might be attributed to the introduction of nitrogen, few of effects and disorder structure. As-prepared N-Gh exhibits low O/C radio that is helpful to maintain high electrical conductivity. And the effects and disorder structure are also conductive to reduce the overlaps of graphene layers. Symmetric supercapacitor assembled with N-Gh electrodes displays satisfactory rate behavior and long cycling stability (92.3% retention after 5000 cycles).